The capture and destruction of Escherichia coli from simulated urban runoff using conventional bioretention media and iron oxide-coated sand - Zhang, Lan (Water environment research : a research publication of the Water Environment Federation, 2010)
The performance, sustainability, and mechanisms of bacterial removal from stormwater runoff by bioretention systems are poorly understood. The potential for removal of microorganisms in bioretention systems was evaluated using column studies and simulated urban stormwater runoff. Conventional bioretention media (CBM) removed 82% of Escherichia coli O157:H7 strain B6914 cells; iron-oxide coated sand (IOCS) significantly enhanced capture, with 99% efficiency. This improvement possibly was because of the greater positive surface charge and roughness, of the IOCS. Trapped strain B6914 cells decayed more rapidly in CBM, however, with more than 99.98% die-off within one week compared with the IOCS in which approximately 48% of trapped cells survived. Predation and competition from native microorganisms in CBM were verified to play a dominant role in rapid destruction of trapped strain B6914. In particular, protozoan grazing appeared to play an important role, with the die-off of trapped B6914 increasing with increasing concentrations of protozoa